The Relationship Between Financial Access And The Gender Unemployment Gap Rate, Women Economic Empowerment And Income Inequality - Eng, Khai Ying (2022)
This thesis examines the implications from financial access to gender unemployment gap rate, women economic empowerment and income inequality. For gender unemployment gap rate and women labour force participation, it is tested by a panel data of 51 countries ranging from 2004 to 2016; for income inequality, a panel data of 48 countries ranging from 2004 to 2016 is employed. The dynamic panel system generalized method of moments (GMM) estimators is used as the analytical tool to answer the research objectives. This method is appropriate to estimate a dynamic panel model and a small panel dataset. A few significance of study can be identified from the objective one gender unemployment gap rate. Related studies, especially those using the number of bank branches and automated teller machines (ATMs) to proxy financial access indicators, are limited. Furthermore, no attempt has been made to compare the effect of financial access on female and male unemployment across a sample of the same countries. The results showed that financial access indicators positively associate with female and male unemployment, probably due to the detrimental effect of financing on job creation. In addition, the positive relationship between employment and financial access is more significant for male unemployment than female unemployment, which might be related to the argument that males are more exposed to formal financial services.